Tobacco abuse among school going adolescents in a rural area of West Bengal, India - Anindya Mukherjee; Abhik Sinha; Pranita Taraphdar; Gandhari Basu; Debadatta Chakrabarty (Wolters Kluwer Medknow Publications, 2012)
Adolescents are vulnerable targets of tobacco industry with all consequences of usage. Studies reveal that tobacco abuse is rising in this age group in India. A cross sectional survey was carried out in two coeducational high schools of Anandanagar village of Singur block, Hooghly district, West Bengal among 276 students of VIII-IX standard to study the knowledge and abuse of tobacco and to find out influencing socio-demographic factors. Knowledge score was higher in females, students from nuclear families, and those with literate parents. Low prevalence of tobacco intake was obtained among the students, with 9.8% reported having ever used smokeless tobacco and 4.3% ever smoked. Tobacco intake was higher among those with a history of parental tobacco intake. Continued information education and communication (IEC) activities should be conducted by the school authorities, with involvement of nongovernment organizations (NGOs) and parents for primary prevention.